Autour de l'Infanterie d'Élite Macédonienne à l'Époque du Royaume Antigonide : cinq études militaires entre histoire, philologie et archéologie - Juhel, Pierre O. (Archaeopress Publishing Ltd, 2017)
This work presents five articles relating to military studies in the context of Macedonia of the Antigonids. Combining literary studies and archaeology, the author proposes several new concepts on Hellenistic Macedonian military studies. Articles consider the Macedonian phalanx, Antigonid Redcoats, heavy infantry and defensive weaponry.